2020
DOI: 10.14336/ad.2020.0309
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs: Promising Biomarkers for Age-related Diseases

Abstract: Aging is a complex biological process closely linked with the occurrence and development of agerelated diseases. Despite recent advances in lifestyle management and drug therapy, the late diagnosis of these diseases causes severe complications, usually resulting in death and consequently impacting social economies. Therefore, the identification of reliable biomarkers and the creation of effective treatment alternatives for agerelated diseases are needed. Circular RNAs (circRNAs) are a novel class of RNA molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 91 publications
1
18
0
Order By: Relevance
“…It is reported that many circRNAs exhibit additional regulatory functions in aging and aging-related diseases progression (26). The present study revealed that circ-Sirt1 was highly expressed in young and healthy arteries, and decreased in aged arteries and in the neointima and atherosclerotic lesion.…”
Section: Discussionsupporting
confidence: 56%
“…It is reported that many circRNAs exhibit additional regulatory functions in aging and aging-related diseases progression (26). The present study revealed that circ-Sirt1 was highly expressed in young and healthy arteries, and decreased in aged arteries and in the neointima and atherosclerotic lesion.…”
Section: Discussionsupporting
confidence: 56%
“…It has been shown that circRNAs are involved with age-related diseases (i.e., cancer, diabetes, osteoporosis, and rheumatoid arthritis [ 73 ]) and are expressed in a development stage-specific manner. It is reasonable to expect that circRNAs involved in periodontal cell differentiation and periodontal regeneration are influenced by ageing and by the stage of development of the periodontium.…”
Section: Discussionmentioning
confidence: 99%
“…At present, however, the function of these RNAs is unknown. CircRNAs might be involved in age-related diseases [ 34 , 35 ]. RNAs of this type may also operate in neuropsychiatric disorders [ 35 ].…”
Section: From Molecules To Extracellular Vesiclesmentioning
confidence: 99%